Hepatic Small Vessel Neoplasm Mimics Prostate Cancer on 18F-DCFPyl PET/CT. (14th April 2023) - Spinali, Keith L.; Papke, David J.; Shah, Hina J.
Abstract: 18 F-DCFPyl is a Food and Drug Administration–approved radiotracer that targets prostate-specific membrane antigen and is used in the detection of recurrent or metastatic prostate cancer. As its use has increased, a growing number of nonprostatic disease entities have been identified that express prostate-specific membrane antigen and can mimic prostate cancer. Thus, the interpreting physician must also consider other variables such as serum prostate-specific antigen levels and the distribution of uptake to avoid an inappropriate diagnosis of metastatic prostate cancer. We describe 18 F-DCFPyl uptake associated with a hepatic small vessel neoplasm, an association previously undescribed in the literature.